Cover Feature: A Mixed‐Metal Porphyrinic Framework Promoting Gas‐Phase CO2 Photoreduction without Organic Sacrificial Agents (ChemSusChem 23/2020). Issue 23 (9th November 2020) - Gao, Wen‐Yang; Ngo, Huong T.; Niu, Zheng; Zhang, Weijie; Pan, Yanxiong; Yang, Zhongyu; Bhethanabotla, Venkat R.; Joseph, Babu; Aguila, Briana; Ma, Shengqian
Abstract : The Cover Feature shows how, serving as an artificial photosynthesis system, the rationally designed Ti/Zr porphyrinic metal–organic framework demonstrates gas‐phase water oxidation‐assisted selective photoreduction of CO2 under visible‐light irradiation. More information can be found in the Communication by W.‐Y. Gao, H. T. Ngo, et al .